Soft and hard carbon composite electrode material applied to sodium ion battery and preparation method of soft and hard carbon composite electrode material

By mixing asphalt with bacterial cellulose aerogel particles and preparing soft and hard carbon composite electrode materials, the existing sodium ion battery negative electrode materials have been solved, and the existing sodium ion battery negative electrode materials have been low specific capacity, unsatisfactory performance and high cost are achieved, and high capacity High magnification and low cost electrochemical properties.

CN119461319APending Publication Date: 2025-02-18HANGZHOU DIANZI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411615344.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode materials, including asphalt-based soft carbon materials and hard carbon materials, have problems such as low specific capacity, poor rate performance and high cost, which limits its application prospects in sodium ion batteries.

Method used

A soft and hard carbon composite electrode material was prepared by mixing asphalt with bacterial cellulose (BC) aerogel particles in a specific proportion, heat treatment and granulation. The material is interwoven by the three-dimensional carbon nanofiber web formed by the carbonized BC aerogel and the soft carbon of the asphalt, improving the electronic conductivity and mechanical structure of the electrode.

Benefits of technology

It realizes the high capacity and high rate performance of the negative electrode material of sodium ion battery, while reducing costs, and has good cycle stability and low cost advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005132048410000011
    Figure HDA0005132048410000011
  • Figure HDA0005132048410000012
    Figure HDA0005132048410000012
  • Figure HDA0005132048410000021
    Figure HDA0005132048410000021
Patent Text Reader

Abstract

The invention relates to the technical field of electrode material preparation, in particular to a soft and hard carbon composite electrode material applied to a sodium ion battery and a preparation method, and asphalt and BC aerogel particles are stirred, heated, cured, granulated and carbonized in a reaction kettle to obtain the soft and hard carbon composite electrode material. The soft and hard carbon composite electrode material applied to the sodium ion battery can be simply and effectively prepared, so that the sodium storage performance is improved. The principle that the obtained soft and hard carbon composite material is high in capacity, high in rate and low in cost lies in that the pitch is low in price but poor in capacity and rate performance, the pitch and BC are fully mixed in a reaction kettle, carbon nanofibers are evenly distributed in the pitch in the carbonization process, and the conductivity of the composite material is improved; on the other hand, due to the existence of the carbon nanofibers, more disordered structures can be generated during high-temperature carbonization of the asphalt, more active sites are provided for embedding of Na < + >, and the capacity is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a soft and hard carbon composite electrode material for sodium ion batteries and a preparation method thereof. Background Art

[0002] Although the energy density of sodium-ion batteries is lower than that of lithium-ion batteries, sodium-ion batteries have cost advantages over lithium-ion batteries and can make up for the shortcomings of lithium-ion batteries to a certain extent in some areas. As one of the important components of sodium-ion batteries, the performance of the negative electrode has an important impact on the overall electrochemical performance and cost of the battery. We hope that the negative electrode material has both excellent electrochemical performance and low cost. Asphalt-based soft carbon materials have the advantages of low cost and good cycle stability, and are a very promising negative electrode material for sodium-ion batteries. However, traditional asphalt-based soft carbon materials are limited in their use prospects due to their low specific capacity and unsatisfactory rate performance. Hard carbon materials are considered to be a type of sodium-ion battery negative electrode material with electrochemical performance superior to soft carbon materials. However, hard carbon materials with excellent electrochemical properties are often prepared from high-cost raw materials, which is contrary to the low-cost advantage of sodium-ion batteries. For example, bacterial cellulose (BC) has a good nano-network structure, and its derived carbon nanofibers have ultra-high conductivity and stability. As a hard carbon negative electrode material, it has a high capacity and good rate performance. However, BC is expensive and has no cost advantage in sodium-ion batteries. This prompted us to develop low-cost and high-performance sodium-ion battery anode materials based on bacterial cellulose and asphalt materials. Summary of the invention

[0003] In order to solve the above-mentioned prior art problems, the present invention provides a method for preparing a soft and hard carbon composite electrode material for sodium ion batteries, comprising the following steps:

[0004] S1, asphalt and BC aerogel particles are mixed in a ratio of 95:5 to 99:1 and placed in a reactor, first stirred at 200°C for 6 hours, then stirred at 600°C for 1 hour, and then naturally cooled to obtain a solidified product;

[0005] S2, granulating the solidified material to obtain carbon powder, wherein the size of the carbon powder is controlled to be between 6um and 8um in d50;

[0006] S3, placing the carbon powder in an atmosphere furnace and heating it at 900°C to 1400°C for 2 hours at a heating rate of 5°C / min, and then cooling it naturally to obtain a soft and hard carbon composite electrode material for sodium ion batteries.

[0007] Preferably, the mixing ratio of asphalt to BC in S1 is any one or more of 95:5, 97:3, and 99:1.

[0008] Preferably, the carbon powder size d50 in S2 is controlled to be one or more of 6um, 7um, and 8um.

[0009] Preferably, the heating process in S3 is carried out in a nitrogen atmosphere.

[0010] Preferably, the heating temperature in S3 is one of 900° C., 1200° C. and 1400° C.

[0011] The present invention also provides a soft and hard carbon composite electrode material for sodium ion batteries, wherein the soft and hard carbon composite electrode material is prepared by the method for preparing the soft and hard carbon composite electrode material for sodium ion batteries as described above.

[0012] The beneficial effects of the present invention are embodied in:

[0013] (1) Excellent electrochemical performance. BC aerogel is formed by interweaving nanocellulose and forming a carbon nanofiber aerogel with a three-dimensional structure after carbonization. In the present invention, the carbon nanofiber network structure formed by the carbonized BC aerogel is interwoven with the soft carbon obtained by carbonizing asphalt to form a soft and hard carbon composite material. The three-dimensional network structure not only improves the electronic conductivity of the electrode material, thereby improving the rate performance of the electrode, but also strengthens the mechanical structure of the electrode material, thereby improving the cycle performance of the electrode.

[0014] (2) Low cost, which is conducive to promoting the application of sodium ion batteries. Although bacterial cellulose is relatively expensive, the proportion of bacterial cellulose aerogel added to asphalt in the present invention is relatively low, which will not cause a significant increase in the cost of the composite material. This not only highlights the improvement of electrode material performance by introducing bacterial cellulose, but also avoids a significant increase in cost.

[0015] The obtained soft and hard carbon composite material has an initial discharge and charge capacity of 363.5 mAh / g and 304.7 mAh / g at 0.1 C, an initial coulombic efficiency of 83.82%, and a discharge and charge capacity of 326.3 mAh / g and 283.6 mAh / g at 1 C. Since the soft and hard carbon composite material provided by the present invention has the characteristics of BC-derived carbon nanofibers and asphalt mixed and co-carbonized, it exhibits excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A schematic diagram of the process for preparing a soft and hard carbon composite electrode material for sodium ion batteries provided by the present invention;

[0017] Figure 2 The first charge and discharge curve of the soft and hard carbon composite electrode material for sodium ion battery prepared in Example 1 of the present invention at 0.1C;

[0018] Figure 3The charge and discharge curves of the soft and hard carbon composite electrode material for sodium ion batteries prepared in Example 1 of the present invention at 1C. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] In order to better illustrate the process and scheme of the present invention, the following invention is further described in conjunction with the accompanying drawings and embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0021] The present invention provides a method for preparing a soft and hard carbon composite electrode material for use in a sodium ion battery, comprising the following steps:

[0022] S1, asphalt and BC aerogel particles are mixed in a ratio of 95:5 to 99:1 and put into a reactor, first stirred at 200°C for 6h, then stirred at 600°C for 1h, and then cooled naturally.

[0023] S2, granulating the solidified product obtained in S1, and controlling d50 to be between 6um and 8um after granulation.

[0024] S3, placing the carbon powder obtained in S2 into an atmosphere furnace and heating it at 900°C to 1400°C for 2 hours at a heating rate of 5°C / min, and then cooling it naturally to obtain a soft and hard carbon composite electrode material for sodium ion batteries.

[0025] In the above technical scheme, the soft and hard carbon composite electrode materials used in sodium ion batteries can be simply and effectively prepared, thereby improving the sodium storage performance. The principle that the soft and hard carbon composite materials obtained by the present invention have high capacity, high rate and low cost is that: asphalt is cheap, but the capacity and rate performance are poor. The asphalt and BC are fully mixed in the reactor, and the carbon nanofibers are evenly distributed in the asphalt during the carbonization process, which improves the conductivity of the composite material; on the other hand, the presence of carbon nanofibers will cause the asphalt to produce more disordered structures during high-temperature carbonization, providing more active sites for the embedding of Na+, effectively improving the capacity.

[0026] Example 1

[0027] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing a soft and hard carbon composite electrode material for a sodium ion battery, comprising the following steps:

[0028] S1, asphalt and BC aerogel particles were mixed in a ratio of 97:3 and put into a reactor, first stirred at 200 °C for 6 h, then stirred at 600 °C for 1 h, and then cooled naturally.

[0029] S2, granulating the solidified product obtained in S1, and controlling d50 to be 8 um after granulation.

[0030] S3, placing the carbon powder obtained in S2 into an atmosphere furnace and heating it at 1400°C for 2 hours at a heating rate of 5°C / min, and then cooling it naturally to obtain a soft and hard carbon composite electrode material for sodium ion batteries.

[0031] Example 2

[0032] S1, asphalt and BC aerogel particles were mixed in a ratio of 97:1 and put into a reactor, first stirred at 200 °C for 6 h, then stirred at 600 °C for 1 h, and then cooled naturally.

[0033] S2, granulating the solidified product obtained in S1, and controlling d50 to be 8 um after granulation.

[0034] S3, placing the carbon powder obtained in S2 into an atmosphere furnace and heating it at 1200°C for 2 hours at a heating rate of 5°C / min, and then cooling it naturally to obtain a soft and hard carbon composite electrode material for sodium ion batteries.

[0035] Example 3

[0036] S1, asphalt and BC aerogel particles were mixed in a ratio of 97:3 and put into a reactor, first stirred at 200 °C for 6 h, then stirred at 600 °C for 1 h, and then cooled naturally.

[0037] S2, granulating the solidified product obtained in S1, and controlling d50 to be 8 um after granulation.

[0038] S3, placing the carbon powder obtained in S2 into an atmosphere furnace and heating it at 900°C for 2h at a heating rate of 5°C / min, and then cooling it naturally to obtain a soft and hard carbon composite electrode material for sodium ion batteries.

[0039] Example 4

[0040] S1, asphalt and BC aerogel particles were mixed in a ratio of 95:5 and put into a reactor, first stirred at 200 °C for 6 h, then stirred at 600 °C for 1 h, and then cooled naturally.

[0041] S2, granulating the solidified product obtained in S1, and controlling d50 at 7 um after granulation.

[0042] S3, placing the carbon powder obtained in S2 into an atmosphere furnace and heating it at 1400°C for 2 hours at a heating rate of 5°C / min, and then cooling it naturally to obtain a soft and hard carbon composite electrode material for sodium ion batteries.

[0043] Example 5

[0044] S1, asphalt and BC aerogel particles were mixed in a ratio of 99:1 and put into a reactor, first stirred at 200 °C for 6 h, then stirred at 600 °C for 1 h, and then cooled naturally.

[0045] S2, granulating the solidified product obtained in S1, and controlling d50 to be 8 um after granulation.

[0046] S3, placing the carbon powder obtained in S2 into an atmosphere furnace and heating it at 1400°C for 2 hours at a heating rate of 5°C / min, and then cooling it naturally to obtain a soft and hard carbon composite electrode material for sodium ion batteries.

[0047] Example 6

[0048] S1, asphalt and BC aerogel particles were mixed in a ratio of 95:5 and put into a reactor, first stirred at 200 °C for 6 h, then stirred at 600 °C for 1 h, and then cooled naturally.

[0049] S2, granulating the solidified product obtained in S1, and controlling d50 at 6 um after granulation.

[0050] S3, placing the carbon powder obtained in S2 into an atmosphere furnace and heating it at 1200°C for 2 hours at a heating rate of 5°C / min, and then cooling it naturally to obtain a soft and hard carbon composite electrode material for sodium ion batteries.

[0051] Example 7

[0052] S1, asphalt and BC aerogel particles were mixed in a ratio of 95:5 and put into a reactor, first stirred at 200 °C for 6 h, then stirred at 600 °C for 1 h, and then cooled naturally.

[0053] S2, granulating the solidified product obtained in S1, and controlling d50 to be 8 um after granulation.

[0054] S3, placing the carbon powder obtained in S2 into an atmosphere furnace and heating it at 900°C for 2h at a heating rate of 5°C / min, and then cooling it naturally to obtain a soft and hard carbon composite electrode material for sodium ion batteries.

[0055] Figure 2The first charge and discharge curve of the soft and hard carbon composite electrode material for sodium ion battery prepared in Example 1 of the present invention at 0.1C. It can be seen that the obtained soft and hard carbon composite material has a first discharge and charge capacity of 363.5 mAh / g and 304.7 mAh / g at 0.1C, and the first coulombic efficiency is 83.82%.

[0056] Figure 3 The charge and discharge curves of the soft and hard carbon composite electrode material for sodium ion batteries prepared in Example 1 of the present invention at 1C. It can be seen that the obtained soft and hard carbon composite material has a discharge and charge capacity of 326.3 mAh / g and 283.6 mAh / g at 1C.

[0057] The performance of the high-capacity, high-rate, low-cost soft and hard carbon composite electrode material obtained in Example 1 was tested. The specific test process is as follows: a half-cell test of the soft and hard carbon composite electrode material applied to sodium ion batteries was used, the negative electrode was a sodium sheet, Celgard2325 was used as a separator, the electrolyte was 1M NaPF6 dissolved in a solution of ethylene carbonate, diethyl carbonate and dimethyl carbonate, and the battery was assembled using a CR2430 coin-type battery shell in a glove box with a humidity and oxygen concentration below 1ppm and full of nitrogen protection. In the charge and discharge test system, the charge and discharge test voltage was 0.01–2V.

[0058] From the above analysis, it can be concluded that the soft and hard carbon composite materials prepared in Example 1 have first discharge and charge capacities of 363.5 mAh / g and 304.7 mAh / g at 0.1C, and a first coulombic efficiency of 83.82%; and have discharge and charge capacities of 326.3 mAh / g and 283.6 mAh / g at 1C.

[0059] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0060] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined in the present invention may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown in the present invention, but will conform to the widest scope consistent with the principles and novel features disclosed in the present invention.

Claims

1. A method for preparing a soft and hard carbon composite electrode material for sodium ion batteries, characterized in that: The following steps are involved: S1, asphalt and BC aerogel particles are mixed in a ratio of 95:5 to 99:1 and placed in a reactor, first stirred at 200°C for 6 hours, then stirred at 600°C for 1 hour, and then naturally cooled to obtain a solidified product; S2, granulating the solidified material to obtain carbon powder, wherein the size of the carbon powder is controlled to be between 6um and 8um in d50; S3, placing the carbon powder in an atmosphere furnace and heating it at 900°C to 1400°C for 2 hours at a heating rate of 5°C / min, and then cooling it naturally to obtain a soft and hard carbon composite electrode material for sodium ion batteries.

2. The method for preparing a soft and hard carbon composite electrode material for sodium ion batteries according to claim 1, characterized in that: The mixing ratio of asphalt to BC in the S1 is any one or more of 95:5, 97:3, and 99:

1.

3. The method for preparing a soft and hard carbon composite electrode material for sodium ion batteries according to claim 1, characterized in that: The carbon powder size d50 in S2 is controlled to be one or more of 6um, 7um, and 8um.

4. The method for preparing a soft and hard carbon composite electrode material for sodium ion batteries according to claim 1, characterized in that: The heating process in S3 is performed in a nitrogen atmosphere.

5. The method for preparing a soft and hard carbon composite electrode material for sodium ion batteries according to claim 1, characterized in that: The heating temperature in S3 is one of 900° C., 1200° C., and 1400° C.

6. A soft and hard carbon composite electrode material for sodium ion batteries, characterized in that: The soft and hard carbon composite electrode material is prepared by the method for preparing a soft and hard carbon composite electrode material for sodium ion batteries as described in any one of claims 1 to 5.